Enhancing dromedary camel (Camelus dromedarius) healthcare: ultrasound-guided diagnostic and therapeutic interventions in the thoracic and abdominal cavities - Tharwat, Mohamed; Barakat, Hassan (Frontiers in Veterinary Science, 2026)
Dromedary camels (Camelus dromedarius) are vital to the socioeconomic and cultural fabric of arid regions, yet their healthcare is less developed than that of other domestic species. Their unique anatomy—including deep thoracoabdominal cavities, thick skin, and dense musculature—challenges conventional diagnostics and interventions. Ultrasound has emerged as a crucial, field-appropriate imaging modality, enabling rapid, non-invasive, real-time visualization of internal structures. This review examines ultrasound-guided diagnostic and therapeutic procedures in dromedary camels. Key diagnostic techniques, including thoracocentesis, abdominocentesis, portocentesis, and organ biopsies, are discussed with respect to clinical indications, protocols, advantages, and potential complications. Ultrasound guidance enhances accuracy and safety by ensuring precise needle placement, minimizing trauma, and improving diagnostic yield. Therapeutic applications, such as pleural effusion drainage and abscess evacuation, highlight ultrasound’s role in minimally invasive alternatives to surgery. Camel-specific anatomical and behavioral factors influencing ultrasonography, including sternal recumbency and adapted equipment, are addressed. Ultrasound features that differentiate types of ascitic fluid—transudates, exudates, and hemorrhagic effusions—are critical for targeted treatment. It also aids in managing complex conditions such as uroperitoneum, peritonitis, and thoracic or abdominal effusions, with ultrasound-guided paracentesis improving differentiation between urinary bladder rupture and obstruction. Challenges remain due to camel anatomy, environmental conditions, sedation risks, and the need for trained operators. Future directions include developing camel-specific protocols, portable devices, AI-assisted and tele-guided diagnostics, and integration into veterinary education. Widespread adoption of ultrasound-guided interventions can enhance camel healthcare, animal welfare, and pastoral livelihoods in arid regions worldwide.